Approaches to kidney replacement therapies—opportunities and challenges - Huang, Biao; Zeng, Zipeng; Zhang, Chennan C.; Schreiber, Megan E.; Li, Zhongwei (Frontiers in Cell and Developmental Biology, 2022)
1 out of 7 people develop chronic kidney disease (CKD). When kidney function continues to decline, CKD patients may develop end-stage renal disease (ESRD, or kidney failure). More than 2 out of 1000 adults develop ESRD and these patients must live on dialysis or get a kidney transplant to survive. Each year, more than $51 billion is spent to treat patients with ESRD in the U.S. In addition, ESRD greatly reduces longevity and quality of life for patients. Compared to dialysis, kidney transplant offers the best chance of survival, but few donor organs are available. Thus, there is an urgent need for innovative solutions that address the shortage of kidneys available for transplantation. Here we summarize the status of current approaches that are being developed to solve the shortage of donor kidneys. These include the bioartificial kidney approach which aims to make a portable dialysis device, the recellularization approach which utilizes native kidney scaffold to make an engineered kidney, the stem cell-based approach which aims to generate a kidney de novo by recapitulating normal kidney organogenesis, the xenotransplantation approach which has the goal to make immunocompatible pig kidneys for transplantation, and the interspecies chimera approach which has potential to generate a human kidney in a host animal. We also discuss the interconnections among the different approaches, and the remaining challenges of translating these approaches into novel therapies.